Survey on positioning technology based on signal of opportunity from low earth orbit - He, Jiawei; Ni, Shaojie; Lin, Honglei; Liu, Zhe; Xiao, Zhibin (Frontiers in Physics, 2025)
Positioning, Navigation, and Timing (PNT) services are essential for supporting various aspects of modern society. Fields such as communications, transportation, and military operations heavily rely on accurate and reliable PNT services, with this dependence expected to grow. However, the limitations of the predominant Global Navigation Satellite System (GNSS) in complex environments have become increasingly apparent. As an effective supplementary approach, space-based signals of opportunity (SOPs) from Low Earth Orbit (LEO) have garnered significant attention. This paper begins by introducing the principle of Doppler location and analyzing its error sources. It then discusses in detail the methods of observation extraction, including cognitive-based and blind-based methods. Focusing on major domestic and international LEO constellations (such as Iridium, Orbcomm, Globalstar, Starlink, OneWeb, etc.), this paper summarizes their signal characteristics and the current status of positioning research, and discusses the latest advancements in observable estimation algorithms. Finally, the paper proposes key research directions for the future, including breakthroughs in satellite recognition technology, optimization of positioning algorithms, development of multi-source fusion positioning technology, and observation extraction in complex environments.